Export Promotion Agencies : What Works and What Doesn’t - Lederman, Daniel (World Bank, Washington, DC, 2012)
The number of national export promotion agencies (EPAs) has tripled over the past two decades. While more countries have made them part of their national export strategy, studies have criticized their efficiency in developing countries (Hogan, Keesing, and Singer 1991). Partly in reaction to these critiques, EPAs have been retooled (see International Trade Centre, ITC, 1998 or 2000, for example). This paper studies the impact of existing EPAs and their strategies based on a new data set covering 104 industrial and developing countries. Results suggest that on average they have a strong and statistically significant impact on exports. For each $1 of export promotion, the paper estimates a $40 increase in exports for the median EPA. However, there is heterogeneity across regions, levels of development, and types of instruments. Furthermore, there are strong diminishing returns, suggesting that as far as EPAs are concerned, small is beautiful.